Technological tools to improve English speaking skill of ninth-grade students at unidad educativa provincia de Cotopaxi during the academic year 2022-2023 - Chochos Toapanta, Mayra Alejandra (2023)
The main objective of this research is to improve English speaking skill through the use of technological tools in the ninth-grade students at Unidad Educativa Provincia de Cotopaxi during the school year 2022 - 2023. Therefore, the researchers designed a theoretical framework where topics and subtopics were classified in a clear and coherent manner to support the research project. Likewise, this project has a quantitative approach since a structured survey of ten questions was applied to twenty students. Additionally, a pre-test was applied to determine the student's level of English, and a post-test was applied to evaluate the improvement of oral expression using eight items, for which the researchers adapted an evaluation rubric to assess the progress of the students. Additionally, the researchers proposed activities that involved the use of the PPP (Presentation, Practice, and Production) method with a CLT (Communicative Language Teaching) approach in relation to technological tools such as Voki, Flipgrid, Duolingo, and Cambridge Dictionary . Finally, the researchers concluded that the use of technological tools improve speaking skills as they improve their social and communicative skills in a fun and motivating way, improving students' confidence and increasing their knowledge of vocabulary, fluency, and even grammar, and even allowing students to learn autonomously.